Mechanisms involved in protection provided by immunization against core lipopolysaccharides of Escherichia coli J5 from lethal Haemophilus pleuropneumoniae infections in swine. - Fenwick, B W (1986)
In an investigation of the potential protective effects of immunity against common lipopolysaccharide core antigens of gram-negative bacteria during a severe gram-negative infection in the natural host, we induced Haemophilus pleuropneumoniae infections in weanling pigs immunized with a vaccine of an Rc mutant of Escherichia coli (strain J5). To help define the mechanism involved in J5-mediated protection, we compared the clinical, hematologic, bacteriologic, and serologic responses following an H. pleuropneumoniae infection in J5-immunized pigs with those following an H. pleuropneumoniae infection in nonimmunized control animals. As a result of an intranasal inoculation, all of the control animals and the J5-immunized animals were infected with H. pleuropneumoniae. However, while 80% (4 of 5) of the nonimmunized pigs died within 24 h as a result of the infection, no deaths occurred in the J5-immunized animals. In the immunized group, J5 titers dropped during the acute stages of the infection and rebounded to well above the prechallenge levels during convalescence. The J5 titer also increased in the single surviving control animal. These findings suggest that antibodies against common subsurface components of gram-negative bacterial cell walls correlate with protection from an otherwise lethal challenge of H. pleuropneumoniae but do not prevent infection. Important growth-phase-dependent antigenic changes have been recognized to occur during the growth of H. pleuropneumoniae in cultures (R. Nielson, Nord. Veterinaermed. 28:337-348, 1976). In a study of these changes and during an inquiry into the mechanism of J5 antibody-mediated protection, measured quantities of H. pleuropneumoniae were removed from a broth culture at hourly intervals and used to absorb hyperimmune equine J5 antiserum. Significantly greater amounts of J5-specific antibodies were absorbed during the log phase of bacterial growth than during the early or late phase. The availability of epitopes recognized by J5 antibodies appears to be closely related to the rate of bacterial multiplication. The results of these experiments suggest a mechanism of protection provided by increased immunity to E. coli J5 during gram-negative infections.